Soybean expansion in Brazil: A quantitative assessment of past technological and environmental changes and implications for future climate change - Abrahão, Gabriel Medeiros (2016)
Brazil is today the world's second largest soybean producer, and the crop is cultivated throughout the country. However, this was not always the case. The most productive soybean regions of today were deemed unsuitable for soybean planting until the 1970's, and the crop was limited to southern Brazil. The new regions were incorporated into production only after significant technological developments on soybean breeding and management practices. The expansion of soybeans into those areas represented a major change in the climate experienced by the plants, and provides important lessons on adaptation to future climate change. This work aims to overcome limitations of data on yields, area and planting dates in order to perform a large-scale quantitative assessment of the changes in climate, photoperiod and technology experienced by soybeans during the expansion, and compare them with future climate expectations. A spatially explicit dataset on soybean harvested area and yields is developed. The photoperiod limitations to the planting date of each year's varieties are estimated using the northernmost latitude where soybeans were planted. This information is combined with spatial rainy season onset and end to obtain spatial and temporal estimates of the planting window for the period 1974- 2012. The estimates compare well with planting dates recommended by the literature. With the development of photoperiod-insensitive varieties, planting windows went from being limited by the photoperiod on most of soybean-producing Brazil in 1974 to be limited by the rainy season in 1984. This development also had the effect of flexibilizing planting dates, making feasible the double cropping systems common today in central Brazil. Soybeans moved to much wetter regions, as total change in average excess precipitation (P-ETC) found was 2.33 mm day -1 on the historical period (1974-2012). Average temperatures rose at a rate of 0.49 °C decade -1 during the expansion, 0.29 °C decade -1 being due to local trends, faster than the expected rate for 2013-2050 (0.35 °C decade -1 ). The highest yields were also achieved in the warmer regions. Funding and coordinating agricultural R&D towards unified goals is likely to be an efficient strategy to adapt Brazilian agricultural systems to climate change, and may bring many beneficial side effects.